Contrasting metacognitive, social cognitive and alexithymia profiles in adults with borderline personality disorder, schizophrenia and substance use disorder. (November 2017) - Lysaker, Paul H.; George, Sunita; Chaudoin–Patzoldt, Kelly A.; Pec, Ondrej; Bob, Petr; Leonhardt, Bethany L.; Vohs, Jenifer L.; James, Alison V.; Wickett, Amanda; Buck, Kelly D.; Dimaggio, Giancarlo
Abstract: Deficits in the ability to recognize and think about mental states are broadly understood to be a root cause of dysfunction in Borderline Personality Disorder (PD). This study compared the magnitude of those deficits relative to other forms of serious mental illness or psychiatric conditions. Assessments were performed using the metacognition assessment scale-abbreviated (MAS-A), emotion recognition using the Bell Lysaker Emotion Recognition Test and alexithymia using the Toronto Alexithymia Scale among adults with schizophrenia ( n = 65), Borderline PD ( n = 34) and Substance Use disorder without psychosis or significant Borderline traits ( n = 32). ANCOVA controlling for age revealed the Borderline PD group had significantly greater levels of metacognitive capacity on the MAS-A than the schizophrenia group and significantly lower levels of metacognitive capacity than the Substance Use group. Multiple comparisons revealed the Borderline PD group had significantly higher self-reflectivity and awareness of the other's mind than the schizophrenia group but lesser mastery and decentration on the MAS-A than substance use group, after controlling for self-report of psychopathology and overall number of PD traits. The Borderline PD and Schizophrenia group had significantly higher levels of alexithymia than the substance use group. No differences were found for emotion recognition. Results suggest metacognitive functioning is differentially affected in different mental disorders. Highlights: It is unknown how metacognitive deficits in Borderline Personality Disorder differ from those in schizophrenia. Metacognition and social cognition in schizophrenia, borderline personality disorder and substance use disorders was compared. Borderline Personality Disorder displayed a unique pattern of metacognitive deficits. Borderline personality disorder may involve uniquely grave metacognitive deficits in decentration and mastery.